Are language rights fundamental - Green, L (Osgoode Hall Law School, 1987)
The rights of people to use their mother tongues are both central to the Canadian constitution and yet seemingly impossible. Their centrality is obvious. The rights of linguistic and religious minorities were the only ones entrenched in the British North America Act that left the usual civil liberties to the protection of common law and party politics. And even with the entrenchment of civil liberties in the Charter, language rights still receive pride of place as even the crudest content-analysis of the document reveals: they occupy sections 16-22 (official language rights), section 23 (minority language educational rights), and more peripherally section 14 (right to an interpreter in trials), and section 27 (preservation of multicultural heritage). This is all the more striking considering that the typical liberal-democratic freedoms of conscience, religion, opinion, expression, assembly and association are jostled together in the brief, telegraphic language of section 2. Language rights enjoy the highest level of constitutional entrenchment. They are exempt from the power of Parliament and the provincial legislatures in section 33 to legislate notwithstanding the Charter. Their amendment requires either unanimous approval of Parliament and the provinces (section 41(c)) or, if the section applies to some but not all provinces, approval of Parliament and all affected provinces (section 43(b)). While some multilingual states, such as Switzerland, appear to flourish with only a minimal degree of constitutional entrenchment, Canada has joined the ranks of Belgium and India with what may seem to be the over-constitutionalizing of language. Thus the historical and political centrality of language rights.